Integrative description of five Pseudechiniscus species (Heterotardigrada: Echiniscidae: the suillus-facettalis complex) - Roszkowska, Milena; Grobys, Daria; Bartylak, Tomasz; Gawlak, Magdalena; Kmita, Hanna; Kepel, Andrzej; Kepel, Marta; Parnikoza, Ivan; Kaczmarek, Łukasz (Zootaxa, 2020)
Pseudechiniscus is a morphologically homogeneous heterotardigrade genus with a relatively low number of morphological features useful for the species discrimination. The species of the Pseudechiniscus suillus-facettalis complex are some of the most challenging tardigrades to identify. Here, we examine several populations from Antarctica, Italy, Madagascar and Norway that would have most likely been attributed to Pse. suillus prior to the recent redescription of the species. Populations were analysed using integrative taxonomy—a combination of classical morphology and morphometry, as well as genetic data. Besides minute differences in dorsal sculpture and morphometry, we found clear, species-specific differences in ventral sculpture which are very useful in discrimination of Pseudechiniscus species. Based on morphology (mainly ventral sculpture) and significant genetic distances in COI and ITS-2 sequences, we describe five new species: Pse. angelusalas sp. nov. from Madagascar, Pse. dastychi sp. nov. from Antarctica, Pse. ehrenbergi sp. nov. from Italy as well as Pse. indistinctus sp. nov. and Pse. lacyformis sp. nov. from Norway. Finally, we provide an updated phylogenetic tree of the genus Pseudechiniscus based on COI sequences.